Antioxidant and anti-inflammatory properties of Punica granatum peel methanolic extract in BV2 microglial cell line - Imam Syafii, Raudhatul Falah; Hassan, Masriana; Azmi, Wafi Mardhiah; Zailan, Nur Fatin Zalikha; Ismail, Rozila; Abdul Rahman, Shamima (Universiti Putra Malaysia, 2021)
Introduction: Punica granatum is a fruit-bearing deciduous shrub or a small tree belonging to the family of L. Punicaceae. Pharmacological activities of P. granatum include antioxidant, anticarcinogenic, and anti-inflammatory properties. The purpose of this study is to investigate the antioxidant and anti-inflammatory properties of P. granatum methanolic extract (PGME) in the BV2 microglial cell line. Method: The bioactive component from P. granatum peel was extracted by a standard methanolic extraction protocol. The antioxidant properties of PGME were analyzed by total phenolic content (TPC) assay, 1,1-dipheyl-2-pycrylhydrazyl (DPPH) free radical scavenging assay, and Ferric Reducing Antioxidant Power (FRAP). The cytotoxicity activity of PGME on BV2 cells was determined by a viability test using MTS reagent. Analyses of the production of inflammatory mediators, including nitric oxide (NO) and cytokines (tumor necrosis factor-alpha [TNF-α], Interleukin [IL]-6 and monocyte chemoattractant protein [MCP]-1) have been carried out to evaluate the anti-inflammatory activity of PGME in LPS-stimulated BV2 cell line. Result: The TPC and radical scavenging activity of PGME increased in a concentration-dependent manner. However, the ferric reducing ability of PGME was slightly lower and no significant difference compared to the reference standard. PGME treatment on the LPS-stimulated BV2 cells significantly inhibits the production of NO and TNF-α and slightly reduced IL-6 level. Conclusion: PGME possesses antioxidative and anti-inflammatory properties. The PGME demonstrated anti-inflammatory activity through inhibition of pro-inflammatory immune mediators on the BV2 microglial cell line. Therefore, we suggest that PGME potentially inhibits oxidative and inflammatory processes.